Factors That Attract Foreign Pharmaceutical Companies Setting Up R&D Center In Malaysia - Hee, Kenneth Kang Koon (2003)
The development of the biotechnology and pharmaceutical industry is far reaching and their broad applications and great impacts have attracted global interest to enter these industries. Pharmaceutical R&D is a costly and risky business, but in recent years the financial rewards from R&D have more than offset its cost and risk. In order to ensure the continuous growth of Malaysia’s economy, the Malaysia government is actively developing these industries to be their star industry in 21st century. One of the challenges for Malaysia is the ability to identify critical success factors to attract foreign pharmaceutical companies to set up R&D center in Malaysia. This study not only aims to discover and understand the factors require by the R&D activities of the pharmaceutical industry in Malaysia. It will also aim to evaluate the choice mode of entry by foreign pharmaceutical companies to set up R&D center into local pharmaceutical industries. Hence, after evaluating factors to attract foreign pharmaceutical companies to operate R&D activities locally, this study would serve as a guideline for the government to develop strategies and successful business policy in order to attract foreign pharmaceutical companies or new market entrants to set up and operate pharmaceutical R&D activities in locally.